RETRACTED - Cell transcription dependent on Wingless-type (Wnt)/beta-catenin in the rat estrous cycle stages - Dağdeviren, Tuğba (The European Research Journal, 2024)
Objectives: We aimed to evaluate how T Cell Factor 7 Like 2 (TCF7L2) and Lymphoid Enhancer Factor-1 (LEF-1), which regulate cell transcription, regulate implantation in the endometrium. Methods: Female rats were determined according to the estrous cycle. The obtained uterine tissues were taken for immunofluorescence staining. Results: In estrous, LEF-1 and TCF7L2 showed localization in perimetrial-myometrial connective tissue. Of all the signaling molecules, the TCF7L2 molecule is the only one that is expressed. Non-expressed TCF7L2 in the uterine epithelium showed strong immunolocalization in the perimetrial myometrial connective tissue and endometrial basal stroma area. LEF-1 was mostly expressed in the metaestrus phase in the areas of gland epithelium. Conclusions: TCF7L2 and LEF-1 play a critical role in cell proliferation, differentiation and transcription by regulating the activation of the Wnt signaling pathway in endometrial cells. These findings help us to understand the role of TCF7L2 and LEF-1 in the provision of endometrial homeostasis and in the implantation process.